2021
DOI: 10.3389/pore.2021.1609941
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination-Related Molecular Subtypes and a Novel Prognostic Index for Bladder Cancer Patients

Abstract: Objective: To develop and validate ubiquitination-related molecular subtypes and a novel prognostic index using ubiquitination-related genes (URGs) for patients with bladder cancer (BCa).Materials and Methods: We downloaded the clinical data and transcriptome data of BCa from TCGA and GEO database. Consensus clustering analysis was conducted to identify ubiquitination-related molecular subtypes for BCa. Besides, we performed univariate and multivariate Cox regression analysis to develop a novel prognostic URGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Several cancers, including bladder cancer and glioma, exhibited immune cell infiltration associated with URGs, which can provide novel therapeutic targets. The common ubiquitination-related subtypes showed significant differences in immune cell infiltration, stromal scores, ESTIMATE scores, and immune scores ( Cai et al, 2021 ). According to the investigation of the immune microenvironment in gliomas, this risk grouping could be used as a guide for common glioma immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several cancers, including bladder cancer and glioma, exhibited immune cell infiltration associated with URGs, which can provide novel therapeutic targets. The common ubiquitination-related subtypes showed significant differences in immune cell infiltration, stromal scores, ESTIMATE scores, and immune scores ( Cai et al, 2021 ). According to the investigation of the immune microenvironment in gliomas, this risk grouping could be used as a guide for common glioma immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of ubiquitination-related regulators in the occurrence and outcome of pancreatic cancer has been deeply researched, which can influence the occurrence, progression, metastasis, and treatment response of various cancers (Ma et al 2020 ; Sun et al 2020 ; Chen et al 2021 ). Ubiquitination-related prognostic signatures have been developed for estimating the prognosis of several types of cancers (Cai et al 2021 ; Wu et al 2021 ; Zhou et al 2021 ). In our research, the expression characteristics and prognostic performances of URGs in PAAD were systematically explored to classify different ubiquitination-related clusters and a novel prognostic signature was precisely established for disease stratification.…”
Section: Discussionmentioning
confidence: 99%
“…The significant role of ubiquitination in cancer development and progression has been demonstrated in multiple reviews, which detailly comments the regulating mechanism of ubiquitination-related biomolecules on neoplastic diseases (Hoeller and Dikic 2009 ; Kirkin and Dikic 2011 ; Lipkowitz and Weissman 2011 ; Deng et al 2020 ). There have been reports that ubiquitination-related regulators are discovered to evaluate the prognostic prediction in renal cell carcinoma and bladder cancers (Cai et al 2021 ; Wu et al 2021 ; Zhou et al 2021 ). Additionally, studies in vivo and vitro display that ubiquitination-related regulators, such as COP9 signalosome complex subunit 6 (CSN6) and F-box protein 22 (FBXO22), participate in the progression of PAAD (Ma et al 2020 ; Chen et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, silencing UBE2T induced cell cycle arrest at the G 2 /M phase and increased apoptosis; thus, it may be considered a potential biomarker and therapeutic target for BC (101). Univariate Cox regression results showed that it was potential ubiquitination-related prognostic molecule, and it was verified to be associated with OS (102). High expression of UBE2T was positively correlated with advanced pathological stage, distant metastasis, histological grade and maximum tumor diameter.…”
Section: Expression Of Ube2t In Cancermentioning
confidence: 91%